Kecenderungan Psikopat pada Remaja di Lembaga Pemasyarakatan Ditinjau dari Kelekatan Anak-Orang Tua - Husnul Khotimah; Sofia Retnowati (Jurnal Psikologi Tabularasa, 2014)
Conducted a variety of deviant behavior of children and adolescents (such as conduct disorder, juvenile delinquency and criminality) have risk factors such as the rise of psychopathic personality disorder. This study aimed to test the hypothesis of attachment relationship of parents to children psychopathic tendencies. The sample was a teenager in prison. Methods of data collection using a scale child-parent attachment and psychopathic tendencies scale. The analysis technique used is regression. The results showed a correlation coefficient (R) of 0.370 with F at 12,380, p = 0.001 (p 0.05), which means that there is a significant correlation between child-parent attachment with psychopathic tendencies in adolescents. Determinant coefficient () of 13.7%, this indicates that the variable child-parent attachment affects the psychopathic tendencies of 13. 7% and 86.3% were influenced by other variables.